Participatory development of Indonesia’s national action plan for zero leprosy: strategies and interventions - Sebong, Perigrinus Hermin; Ferdiana, Astri; Tegu, Florisma Arista Riti; Harbianto, Deni; Soviandhi, Ronny; Sinaga, Asken; Budiawan, Teky; Risnanto, Arnoldus Janssen Angga Yanuar; Sidjabat, Regina Tiolina; Yudopuspito, Trijoko; Mawardi, Ridwan; Setyawati, Eny; et al. (Frontiers in Public Health, 2025)
RationaleLeprosy remains a significant public health problem in Indonesia, with 14,000–15,000 new cases reported each year, indicating ongoing transmission. In response to the challenges, the country needs a strategic approach to achieve zero leprosy by 2030 through creating a national action plan.ObjectiveTo describe the development of a national action plan for leprosy in Indonesia, its strategies, and key interventions.MethodsThe process of NAP-L development consisted of three phases: (1) the preparatory phase involving 78 participants in five online group discussions (OGD) and document reviews to gain an understanding of the current situation of leprosy control; (2) the implementation phase, involving eight workshops with representatives from 14 provincial health offices, six district health offices, and 78 stakeholders to discuss stakeholder mapping and key components in the national action plan; and (3) the finalization phase to produce the complete document. All workshops and OGDs were audio-recorded. Verbatim transcripts were produced from the OGDs, and a thematic qualitative analysis was carried out to identify codes and categories of barriers to leprosy control. Each workshop’s summary was documented.ResultsBarriers to leprosy control were categorized into program inputs, implementation barriers from demand and supply perspectives, and proposed improvements. Four innovative strategies were formulated. The strategies were: (i) mobilizing various community resources (community); (ii) increasing the capacity of the healthcare system in the prevention, early detection, diagnosis, and management of leprosy in a comprehensive and quality manner (acceleration); (iii) improving integration and coordination with stakeholders and public-private healthcare providers (integration); and (iv) strengthening commitment, policy, and leprosy program management (commitment, policy, and management). Twenty-one key interventions and three measurable outcomes were proposed.ConclusionThe national action plan for leprosy control was developed through a participatory process involving multiple stakeholders from health and cross-sectors, public and private sectors, healthcare providers, community leaders, and persons affected by leprosy. To ensure successful implementation, a national monitoring and evaluation framework should be established to keep track of the progress and local governments should adopt the national action plan into their local health policies.